New multiple aperture arrangements for speckle photography (2000)
Abstract. We propose a multiple exposure specklegram by using an optical system whose multiple aperture pupil changes between exposures. In particular, we analyze experimentally two arrangements and we show that it is possible to store the required information by employing a minimum number of registers if an adequate selection of the pupil is done. We study the effect of the decorrelation (among the stored speckle pattern) introduced by changing the multiple aperture pupil arrangements between exposures. The fundamentals and the relative benefits of the new scheme proposed are discussed on the basis of a fringe visibility analysis.